Avaliação da resistência ao desgaste de novas ligas de titânio para aplicações em indústrias automotiva/aeronáutica/aeroespacial - Putini, Daluan Moreno Esperândio (2019)
Although titanium and its alloys are known for their good corrosion resistance and high strength-to-weight ratio, these materials have low wear resistance. Metallic matrix composites are materials containing dispersed precipitates that can contribute to increase the wear resistance of components used in the automotive / aeronautical / aerospace industries. In this context, the present work aimed at the preparation of new titanium alloys formed by metallic matrix and precipitates of intermetallic phases, which had their wear behavior evaluated, which had their wear behaviors evaluated in a quantitative and qualitative way. High purity raw materials were used for the preparation of Ti-6Zr-2Si-1B, Ti-6Zr-6Si-3B and Ti-6Zr-10Si-5B alloys by arc melting and subsequent heat treatment (1100ºC for 4h + 1150ºC for 16h), in order to obtain equilibrium microstructures. Samples of the thermally treated alloys were evaluated by scanning electron microscopy, dispersive energy spectrometry, X-ray diffraction and Vickers microhardness. After machining, samples of the Ti-Zr-Si-B alloys were subjected to ball-on-disk wear tests in a tribometer according to ASTM G99-95a, which were conducted in different media (dry, solution of NaCl and automotive lubricating oil) and using alumina sphere (10 mm in diameter) as against backing. In these reciprocal slip tests, 10 N axial load and a frequency of 4 Hz were adopted. Thus, tracks of about 4 mm in length were produced on the surface of thermally treated Ti-Zr-Si-B samples. Information on the volume of material removed from the worn surface was calculated, while the wear mechanisms involved were evaluated by scanning electron microscopy. The microstructures of thermally treated Ti-Zr-Si-B alloys indicated the presence of the following phases: α-Ti (matrix), (Ti, Zr)3Si and TiB. Regardless of the chemical composition, the results indicated that the highest coefficients of friction were found in dry-run tests, which were reduced when evaluated in NaCl media and lubricating oil. It was also noted that the formed phases directly influence the coeficients of friction when evaluated in lubricating oil. Consistently, increasing the amount of Si and B produced harder materials due to the greater amount of the intermetallic phases formed in the microstructure. The surfaces of the worn samples revealed the occurrence of both adhesion and abrasion mechanisms, becoming more pronounced for Ti-6Zr-2Si-1B and Ti-6Zr-10Si-5B alloys, respectively.